Application of ultrasound in a congenital cystic adenomatoid malformation in an adult: A case report. Issue 49 (4th December 2020) - Xu, Wen; Wen, Qing; Zha, Lijing; Liu, Chunmei; Huang, Pintong
Abstract: Introduction: Congenital cystic adenomatoid malformation (CCAM) is a rare developmental lung abnormality, that typically manifests in neonates and infants but rarely in adults. Ultrasound is an important method of diagnosing CCAM in neonates and infants; however, few articles have reported the value of transthoracic lung ultrasound in the diagnosis of CCAM in adults. Patient concerns: We present a case of a 34-year-old woman with a cavitary lesion in her left lower lobe, that suggested chronic inflammation. Diagnosis: The patient underwent ultrasound examination and contrast-enhanced ultrasound-guided transthoracic core biopsy; histology suggested the diagnosis of lung hamartoma. Surgical resection of the lesion followed by histopathological analysis confirmed the diagnosis of CCAM. Interventions: The patient underwent transthoracic core biopsy under contrast-enhanced ultrasound guidance. A left lower lobectomy was then performed subsequently. Outcomes: The patient had a smooth recovery and remained asymptomatic during the 12-months of postoperative follow-up. Conclusion: We report a rare case of CCAM to suggest that transthoracic ultrasound combined with contrast-enhanced ultrasound is a safe and effective method of diagnosing the subpleural lung malformations in adults, thereby avoiding multiple radiation exposures and associated complications.